2019
DOI: 10.1111/jgh.14837
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative prediction of futile surgery in patients with radiologically resectable or borderline resectable pancreatic adenocarcinoma

Abstract: Background and Aim The aim of this study is to identify the predictive factors for futile surgery in patients with radiologically resectable or borderline resectable pancreatic cancer and to develop a prediction model. Methods This retrospective study included patients who underwent pancreatic surgery for pancreatic cancer between 2006 and 2017. To identify independent risk factors for futile surgery, logistic regression and random forest analyses were performed in the training cohort, based on which a nomogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 26 publications
(46 reference statements)
1
9
0
Order By: Relevance
“…A couple of factors have been reported to be associated with occult metastatic disease, including younger age, male sex, weight loss, larger tumor size, higher CA19-9, suspicious lymph node and more extensive peripancreatic tumor infiltration et al (4,6,9,26). Our study showed that ALT >40 U/L, CA19-9, CA125 and regional nodes enlargement were independent predictors for occult metastasis.…”
Section: Discussionsupporting
confidence: 59%
“…A couple of factors have been reported to be associated with occult metastatic disease, including younger age, male sex, weight loss, larger tumor size, higher CA19-9, suspicious lymph node and more extensive peripancreatic tumor infiltration et al (4,6,9,26). Our study showed that ALT >40 U/L, CA19-9, CA125 and regional nodes enlargement were independent predictors for occult metastasis.…”
Section: Discussionsupporting
confidence: 59%
“…Few studies have reproduced the insignificant prognostic value of extrapancreatic extension, 7 whereas several studies have demonstrated otherwise. 3,8,9 The greatest advantages of removing extrapancreatic extension and categorizing based on size alone are preventing the majority of tumors from being categorized as T3 and increasing the reproducibility of staging. [12][13][14] However, although limited to T1 pancreatic cancer, this study has demonstrated the prognostic relevance of extrapancreatic extension through survival analysis and multivariate analysis.…”
Section: Discussionmentioning
confidence: 99%
“…However, the details of relevant results were not presented in the article. Furthermore, a limited number of studies were able to reproduce the prognostic insignificance of extrapancreatic extension, 7 whereas other studies have reported contrary results 3,8,9 . Therefore, the feasibility of this change needs to be re‐examined using a reliable dataset of T1 pancreatic cancer cases.…”
Section: Introductionmentioning
confidence: 99%
“…Second, the aggressive nature of surgery for PDAC, which is pylorus-preserving pancreaticoduodenectomy, prevents patients from receiving adjuvant chemotherapy with surgery-related morbidity and complications. 6,7 According to previous studies, only 26% to 74% of patients receive postoperative therapy because of postoperative complications, reduced performance status, and early disease recurrence. [8][9][10][11] Neoadjuvant therapy for PDAC has been considered an alternative option in borderline resectable/locally advanced PDAC.…”
Section: Introductionmentioning
confidence: 99%